Propuesta culinaria mediante la aplicación del tzawar mishki en la repostería ecuatoriana - Fueres Tituaña, Dayana Abigail (2023)
The tzawar mishki is a drink that represents an important cultural and gastronomic legacy for the peoples of the Ecuadorian highlands\; due to its sweet taste, it is considered the first natural sweetener used in the kitchen even since pre-Hispanic times, the knowledge that exists about this superfood is transmitted by those who still preserve this tradition. However, the consumption of this beverage has been declining because ancestral knowledge has been gradually lost. In this context, the present work proposed to use the tzawar mishki in the preparation of ten Ecuadorian desserts in order to diversify the offer in Ecuadorian gastronomy. On the other hand, the methodology corresponds to applied research with a mixed approach\; in addition, the following methods were implemented: the inductive deductive method to gather information on tzawar mishki and the analytical-synthetic method to analyze its application in Ecuadorian desserts. For the field study, the techniques that were carried out were: the survey directed to 382 people belonging to the Economically Active Population (EAP) of the Otavalo canton\; the interview that was carried out to five tzawar mishki collectors and the observation technique carried out by means of an observation card. Among the most important results of this research was the list of desserts: arroz de leche, come y bebe, espumilla, dulce de higos con queso, humitas, morocho, pristiños con miel, empanadas de dulce de sambo, quimbolitos and torta de maqueño. During the preparation of the desserts, it became evident that the tzawar mishki should be boiled before application, because it is a product of rapid fermentation and alters the flavor of the desserts.